Community, Education, and Technology in Language Revitalization: A Narrative Review - D, Rajkamal; Susanti, Arik (Indonesian Scientific Publication, 2025)
Endangered languages are among the most critical challenges in preserving human cultural and intellectual diversity. More than 40% of the world’s 7,000 languages are currently at risk of extinction. This narrative review examines global strategies for language revitalization, focusing on the roles of communities, education, technology, policy, and cultural identity. Literature was gathered from major academic databases (Scopus, PubMed, Google Scholar) using core keywords such as language revitalization and endangered languages. The findings show that community-based initiatives, such as language nests and cultural integration, are crucial for intergenerational transmission. Education policies that include minority languages in school curricula foster measurable gains, while the absence of institutional support often results in stagnation. Digital tools expand access and engagement, though their effectiveness depends on cultural adaptation and community participation. Government recognition and funding further determine success, with marked disparities between developed and developing regions. Overall, language revitalization is not only a linguistic concern but also a matter of identity, cultural resilience, and social justice.